On the banks of Plum Creek - Wilder, Laura Ingalls, 1867-1957. (New York : HarperTrophy, 1971)
Ma, Pa, Laura, Mary, and Carrie settle on the prairie land of Minnesota where runaway cattle, wolves, torrential creeks, a grasshopper plague, and a long blizzard offset the joys of a new house, school friends, and church socials.
First published: 1937.
Book Links (A.L.A.).
Library Journal.
Newbery Medal/Honor.
Book Links (A.L.A.), July 2004.
Horn Book, December 2005.
Keywords: Frontier and pioneer life -- Fiction; Historical fiction; Frontier and pioneer life -- Fiction; Historical fiction; Minnesota -- History -- Fiction; Minnesota -- History -- Fiction